Forest Change Monitoring and Environmental Impact in Gunung Palung National Park, West Kalimantan, Indonesia - Nurul Ihsan Ihsan Fawzi; Angela Meike Indrayani; Keva DeKay (School of Postgraduate Studies, Diponegoro Univer, 2019)
Gunung Palung National Park were protected since 1937 and become remain conserve largest dipterocarp forest in Borneo. The park has severe forest loss caused by anthropogenic activities and forest fire. To help inform conservation efforts about pattern and distribution of deforestation in the park, we measured forest cover change in the protected area using 11 multi-temporal Landsat series images with path/row 121/61. We found the park already loss 10.68% of its forest area in 1989 and 26% from an initial loss in 1989 in 1997 caused by El Niño event. Currently, deforestation rate is 0.21%, higher than global rate cause El Niño of 2015/16 event and make severe forest fire. The direct impact of deforestation and or degradation in a protected area is biodiversity loss and shortage water storage or flooding. This biodiversity loss created by habitat loss, fragmentation, or genetic drifting. Different wildlife and vegetation have a different response for habitat change and will reach the new equilibrium.